2019
DOI: 10.3390/insects10070189
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Insect Growth Regulators on Stephanitis pyrioides (Hemiptera: Tingidae) Eggs and Nymphs

Abstract: The azalea lace bug, Stephanitis pyrioides (Scott) (Hemiptera: Tingidae), is an important insect pest of azaleas (Rhododendron L. spp.) in the USA. Stephanitis pyrioides feeds on azalea foliage and causes extensive chlorosis, which reduces the aesthetic value and marketability of these plants. Because the use of neonicotinoid insecticides has been dramatically reduced or discontinued, growers and landscape managers are seeking alternative tools or strategies to control this insect. Although insect growth regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…The leaves treated with novaluron alone and novaluron with any adjuvant exerted similar effects on nymphal densities. In contrast, a previous study showed that adding an adjuvant improved the ovicidal activity of novaluron in S. pyrioides [18]. This suggests that adding an adjuvant to novaluron may present value in suppressing the S. pyrioides population in the long run.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…The leaves treated with novaluron alone and novaluron with any adjuvant exerted similar effects on nymphal densities. In contrast, a previous study showed that adding an adjuvant improved the ovicidal activity of novaluron in S. pyrioides [18]. This suggests that adding an adjuvant to novaluron may present value in suppressing the S. pyrioides population in the long run.…”
Section: Discussionmentioning
confidence: 70%
“…This means that the deposited novaluron residues are not required to travel through several cell layers to be accessible to adults and nymphs of S. pyrioides. Although the length of the stylets may be shorter in the first and second instars of S. pyrioides than in adults, the effects of novaluron were evident even in young nymphs [18], which suggests that novaluron without any adjuvant can cross the leaf blade and intoxicate young nymphs through ingestion. A previous study also showed that young instars directly exposed to novaluron residues on the leaf surface did not exhibit mortality [18].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations